924 EXPERIENCES OF HEALTH SERVICE USE FOR PEOPLE LIVING WITH PARKINSON'S DISEASE: A NATIONAL SURVEY. (14th June 2022) - O' Shea, E; Rukundo, A; Timmons, S
Abstract: Introduction: Despite the growing prevalence of Parkinson's disease (PD), and the need to plan for future health service provision, very little is known in the Irish context about PD patients' experiences of health service access and use. Method: A cross-sectional survey design, with multiple formats, i.e. online, pen-and-paper, and telephone. Data were collected from May 2020–July 2021 using a multipronged recruitment strategy. It could be completed by a person with PD, or a support person on behalf of/with the person. Survey development was informed through literature review, and in consultation with the Parkinson's Association of Ireland, and a patient advisory group (N = 10). Results: A total of 1, 504 individuals accessed the survey, with 1, 402 meeting the eligibility criteria. Over half (53%) were male. Approx. 9% were diagnosed with young-onset PD. A minority (6%) reported attending only their GP to manage their PD, with the rest attending a specialist outpatient clinic. The mean distance travelled each-way to outpatient clinics was 45.6 km (SD = 49.4, min 1 km, max. 300kms). Most were diagnosed by Neurologists (84%), followed by GPs (8%), and Geriatricians (7%); 1% indicated 'other'. Of those diagnosed by a Neurologist or Geriatrician, most were diagnosed privately (68%); though 37% of these patients subsequently switched to the public system for ongoing management. The majority (97%) reported currently taking PD medications, but just 52% believed these were working effectively. Just over one-fifth (22%) had access to a PD nurse specialist. Access to the range of other health and social care professionals is also reported, and is universally poor for this patient group. Conclusion: A number of significant gaps in PD care have been identified, which require urgent attention. A reconfigured model of PD care is necessary to accommodate the growing need for specialist, integrated care at the population level.